An approach to generalized holomorphic functions - Soares, Marcelo Reicher [UNESP] (Taylor & Francis Ltd, 2011)
A study of the generalized holomorphic functions, HG(Omega), having in mind its strict elements, i.e. those which are in HG(Omega) - H(Omega), as well as the possibility of the existence of hybrid elements, i.e. elements which have, in a part of a domain Omega subset of C-n, the strict behaviour and, in another part of the same domain, the classical behaviour, is carried out in this work. The study of hybrid elements is important in the approach of a concept of generalized domain of holomorphy.
Keywords: holomorphic generalized functions; hybrid functions; Heaviside cut function